327 Relative Benefits of Extracorporeal Shockwave Lithotripsy (ESWL) Compared to Observation in Acute Renal Colic. (12th October 2021) - Lovegrove, C; Spencer, M; Turney, B; Neal, N
Abstract: Aim: NICE guidance recommends patients with renal colic be offered surgical treatment, including extracorporeal shockwave lithotripsy (ESWL), within 48 hours if pain is uncontrolled or stones unlikely to pass. We compared outcomes for ureteric stone passage after ESWL with those of observation to ascertain the relative benefits of ESWL. Method: We collected data on stone location, size, and number of ESWL treatments required prospectively over 18 months. Stone passage was confirmed radiologically. Data were compared with MIMIC, a multi-centre collaborative study examining spontaneous stone passage after observation alone. Results: 166 patients had ESWL for ureteric stones. Median size was 6.5mm (IQR 5.0-8.0mm). 57.2% (N = 95) were proximal stones. Smaller stones required fewer treatments (P = 0.003). Patients with a ureteric stone <5mm required median 1.0 ESWL treatments (IQR 1.0-2.0). Ureteric stones 5-7mm had median 1.0 treatments (IQR 1.0-2.0) and stones >7mm median 2.0 treatments (IQR 1.0-2.0). Compared to MIMIC, patients with ESWL for stones <5mm were 11% more likely to achieve stone clearance (100.0% vs 89.0%, P = 0.001). ESWL for 5-7mm stones had 28.1% greater clearance compared to observation (77.1% vs. 49.0%, P < 0.001) and ESWL for stones >7mm 21% greater likelihood of clearance (50.0% vs. 29.0%, P < 0.001). Proximal ureteric stones were 16.4% more likely to pass with ESWL than observation (68.4% vs 52%, P = 0.02). Distal stones showed similar passage with ESWL (77.5%) and observation (83.0%), P = 0.43. Conclusions: Proximal ureteric stones and those >5mm stones benefit most from ESWL. Results aid identification of patients whose stones are less likely to pass and warrant urgent review to consider ESWL.